(3TQM GdMeGSIs - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3CMeO Hf eMeO Hf HdGd Hf GdMGQK GdeOfi GdbGjfi s)
(3ChdgG (B:s
(3bGd GdTjN GdNWjH GdJHQjRi COGe Gddg Jecjfg , GeG HYO MeO Gddg hGdUdGI Ydi fHjg eMeO hBdg , aEfi cfJ cJHJ ddMeGSg TQMkG eSJhai s
(3BNQgG (B:s
(3hGdKGdK bhd GdeNRhejI(B: (3Ef JSCdi aGdeLO ZjQ bO Md ai Jje heNRhe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs